La protesta estudiantil en Chile (2011)
ABSTRACT: It was developed in the Chile of 2011, a new social process: the social protest that heads the Chilean students who have managed to install the necessity of a deep change in Chile. One has taken place what until recently it was considered impossible: that a clear majority shares the idea that economic, social, institutional and cultural the model that restored the military dictatorship and that was guaranteed by twenty years of government of the Concertacion must be modified until in its roots open passage to social justice. This demand by the change, from the exigency of equality of rights in the education, cradle in one based denunciation of the inequality and discrimination that suffers vast sectors of Chileans in education, health, house, wages, etc., has taken place in a praised country of Latin America like example by its model of market economy. The students have been asking themselves, if for forty years, when the country was poorer, the education was gratuitous, what has passed with the development and the high indices of growth? , where it is the money of the progress? If the mobilizations have been so strong it also must to the unjust thing of the Chilean educational model, implanted by the dictatorship and developed by the civil governments happened who it. A stage of the history of the country is finishing. One began more ago than twenty years and has included five governments. It began full of hopes when the Chileans put aim in 1988 to a dictatorship. Beyond its profits, the postdictatorial stage accumulated hopelessness and frustration. The realised promises have not consolidated a deeply unjust society.